Fictional photography in Japan at nineteenth-century, scene’s reconstructions for the western market - M. Carmen CABREJAS ALMENA (Anales de Historia del Arte, 2010)
The article analyzes the emergence and development of a type of fictional photography (the reconstruction of genre scenes and types) in Japan during the 19th Century, related to the fact that the photographic production was directed to the Western market. This includes the characteristics and themes which were exploited in these images for the Western viewer.